DO ACTIONS SPEAK LOUDER THAN WORDS? FACTORS THAT CHANGE HOW OBJECTIVE PREDICT SUBJECTIVE DRIVING BEHAVIORS. (11th November 2018) - Vivoda, J; Molnar, L J; Eby, D W; Bogard, S; LeBlanc, D; DiGuiseppi, C; Zakrasek, J; St. Louis, R M
Abstract: Self-reported measures of driving behavior are often relied upon in research. Such measures are known to be significantly related to objective driving behavior, but little is known about what other factors may play a role in how well objective predict subjective measures. Data from the Longitudinal Research on Aging Drivers (LongROAD) study were used to assess the moderating role played by demographics, cognition, and driving comfort and ability, in this relationship. Common driving avoidance behaviors (e.g., nighttime driving) and exposure were analyzed. Objective measures were derived from vehicle GPS data; subjective measures were assessed via a questionnaire. Regression analyses assessed statistical interactions between the objective measure and each demographic, cognitive, and driving factor in predicting the subjective measure. Results identified significant interactions with gender, age, race, work status, driving comfort, and driving ability. A composite measure of objective/subjective match was also assessed, with driving comfort playing a particularly important role.